Project Management Maturity. - Walker, Derek (Emerald Group Publishing Limited, 2014)
This e-book presents a global perspective on research in the area of Project Management Maturity. The area is one of great interest as evidenced by the numerous submissions from researchers and practitioners working in a number of countries. The final e-book reflects this great global interest, with contributions drawn from Australia, Indonesia, the United Arab Emirates and Europe. The chapters in this e-book present a range of conceptual and empirical papers, extending the body of academic knowledge in Project Management maturity. The level of interest indicate that this topic will only grow.